RANCANG BANGUN APLIKASI PENGENDALIAN PERSEDIAAN BAHAN BAKU PADA CV BINA RUKUN - Boga, Anto; Supriyanto, Antok; Setyawan, Henry Bambang (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
CV. Bina Rukun is a company engaged in manufacturing namely paper processing raw materials into semi-finished to bag of souvenirs and printing and paper cutting services to the motif of a bag of souvenirs.In a day CV Bina Rukun produces raw materials semi-finished paper a number of 3000 kg/day. Inventory is very important in CV Bina Rukun to maintain stability or smooth production operation company and remove risk delay the coming the raw materials that needed. Demand for the number of the raw material that uncertain in any stretch out part of the barn is make difficulties in estimating the amount of the needs of raw materials to the future. Incorrectness in determining the time of reserving resulting in running out of stock and delay filling orders raw materials half-baked for customers.Based on problems going on up , can be given a solution that CV Bina Rukun need an application that can help in the process of control supplies raw materials that is , help determine how many the amount of raw will ordered and when they do it reservations repeated to the raw materials.Based on the results of the tryouts that have been made this application can solve the problems occurring by means of help determine how many the amount of raw will ordered and when they do it reservations repeated to raw materials. It is in good trial results by application by using black box testing by focusing on testing the function of the input of user in the system that gets the value of 100% means the application is worth used.